The first Large Flake Acheulean in Europe at Revilleja de Valparaíso site, Hortigüela, Spain - Francisco-Javier García-Vadillo; Eudald Carbonell; Xosé-Pedro Rodríguez-Álvarez; Alfonso Benito-Calvo; Régis Braucher; Davinia Moreno; Isabel Hernando-Alonso; Rodrigo Alonso-Alcalde; Marta Navazo-Ruiz; Antoni Canals-Salomó (Quaternary Science Reviews, 2026)

Does knowledge influence visual attention? A comparative analysis between archaeologists and naïve subjects during the exploration of Lower Palaeolithic tools - María Silva-Gago; Annapaola Fedato; Marcos Terradillos-Bernal; Rodrigo Alonso-Alcalde; Timothy Hodgson; Emiliano Bruner (Archaeological and Anthropological Sciences, 2022)
The role of experience during the exploration of lithic artefacts can be been investigated through multiple approaches. Knowledge can influence visual perception of the environment, whilst action “affordances” can be processed at the first sight of an object. In this study, we used eye tracking to analyse whether and to what extent archaeological knowledge can influence visuospatial attention whilst interacting with stone tools. Archaeologists were found to pay more visual attention to the middle region and the knapped surface. Differences between the visual exploration of choppers and handaxes were also found. Although the general pattern of distribution of the visual attention was similar to naïve subjects, participants with archaeological experience paid more attention to functionally relevant regions. Individuals with archaeological experience directed more attention to the upper region and the knapped surface of the tools, whilst naïve participants spent more time viewing the middle region. We conclude that although both groups could direct their attention to action relevant features in stone tools, functional affordances had a greater effect in subjects with previous experience. Affordances related to manipulation triggered lower attention and showed no differences between participants.

Visual attention reveals affordances during Lower Palaeolithic stone tool exploration - María Silva-Gago; Annapaola Fedato; Timothy Hodgson; Marcos Terradillos-Bernal; Rodrigo Alonso-Alcalde; Emiliano Bruner (Archaeological and Anthropological Sciences, 2021)

Hand grasping and finger flexion during Lower Paleolithic stone tool ergonomic exploration - Annapaola Fedato; María Silva-Gago; Marcos Terradillos-Bernal; Rodrigo Alonso-Alcalde; Emiliano Bruner (Archaeological and Anthropological Sciences, 2020)